Digital computer electronics - Malvino, Albert Paul. (New York : McGraw Hill Education, 1977)
This book is for introductory courses in universities, community colleges, and technical institutes.
Chapter 1. Binary numbers -- 2. Logic circuits -- 3. More logic circuits -- 4. Arithmetic circuits -- 5. Flip-flops -- 6. Registers -- 7. Memories -- 8. SAP-1 -- 9. SAP-2 -- 10. SAP-3.
Includes index.
Keywords: ELECTRONIC DIGITAL COMPUTERS